2014
DOI: 10.1007/7651_2014_88
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Autoimmune Encephalomyelitis in Mice

Abstract: Experimental autoimmune encephalitis (EAE), the animal model of multiple sclerosis (MS), has provided significant insight into the mechanisms that initiate and drive autoimmunity. Several central nervous system proteins and peptides have been used to induce disease, in a number of different mouse strains, to model the diverse clinical presentations of MS. In this chapter, we detail the materials and methods used to induce active and adoptive EAE. We focus on disease induction in the SJL/J, C57BL/6, and BALB/c … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 58 publications
(17 reference statements)
0
55
0
Order By: Relevance
“…CNS-immune cells were isolated by Percoll gradient centrifugation from homogenized combined brain and spinal cords as previously described [20]. The numbers of cell subpopulations in the CNS were determined by multiplying the percentage of lineage marker—positive cells by the total number of mononuclear cells isolated from the CNS.…”
Section: Methodsmentioning
confidence: 99%
“…CNS-immune cells were isolated by Percoll gradient centrifugation from homogenized combined brain and spinal cords as previously described [20]. The numbers of cell subpopulations in the CNS were determined by multiplying the percentage of lineage marker—positive cells by the total number of mononuclear cells isolated from the CNS.…”
Section: Methodsmentioning
confidence: 99%
“…Spinal cords (SC) were harvested intact at disease peak and relapse by flushing the vertebral column with saline (37), then fixed in 4% paraformaldehyde overnight at 4°C. This method removes the meninges.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple sclerosis (MS) is a chronic autoimmune neuroinflammatory disease that leads to multifocal demyelination in the white matter of the human CNS with debilitating motor and sensory dysfunction (44, 45). Previous studies using EAE, a mouse model for MS, have shown that DCs play a critical role in initiation and development of CNS pathology through activation of effector T cells in the draining lymph nodes (DLN) and CNS (44, 45).…”
Section: Wnt/β-catenin Signaling In Dcs: a Potential Therapeutic Targmentioning
confidence: 99%
“…Previous studies using EAE, a mouse model for MS, have shown that DCs play a critical role in initiation and development of CNS pathology through activation of effector T cells in the draining lymph nodes (DLN) and CNS (44, 45). These studies have shown that DCs contribute to CNS pathology through differentiation and activation of naive CD4 + T cells to myelin-specific effector Th1 and Th17 cells (44, 46).…”
Section: Wnt/β-catenin Signaling In Dcs: a Potential Therapeutic Targmentioning
confidence: 99%